Association between serum levels of pro-metalloproteinase 1, tissue inhibitor of metalloproteinases 1 and 2 and prevalent cardiovascular disease in a population-based study - Panayiotou, Andrie G.; Kamilari, E.; Griffin, Maura B.; Tyllis, Theodosis H.; Georgiou, Niki; Bond, Dawn; Hoppensteadt, Debra A.; Fareed, Jawed; Nicolaides, Andrew N. (My University, 2013)
Aim: The aim of the study was to test the association between circulating levels of matrix prometalloproteinase1 (pro-MMP1) and its tissue inhibitors TIMP1 and TIMP2 with prevalent cardiovascular events. Methods. Prevalent cardiovascular events were documented in 500 participants of the Cyprus study (46% men) over the age of 40. Serum levels of pro-MMPl, TIMP1 and TIMP2 were measured with ELISA and the association between quartiles of serum levels and presence of cardiovascular disease (CVD) was tested using multivariable binary regression models. Results: Lower serum levels of pro-MMPl and TIMP1 were strongly associated with presence of CVD at baseline even after adjustment for conventional risk factors (Pfor trend=0.006 and P=0.001, respectively) and inflammatory factors (Pfor trend=0.005 and P=0.002, respectively) with people in the highest quartile of pro-MMP1 having a reduced odds for cardiovascular disease by about 70% compared to the lowest quartile (ORadjusted=0.26; 95% CI=0.19 to 0.75; P=0.01), whereas people with TIMP1 levels >11000 ng/mL had a 75% reduced odds for CVD compared to the rest (ORadjusted =0.25; 95% CI=0.11 to 0.60; P for trend=0.002). TIMP2 levels were not associated with prevalent cardiovascular disease. Conclusion. A strong association between lower levels of circulating pro-MMP1 and TIMP1 and risk of prevalent cardiovascular disease in a general population cohort over 40 years is evident, independent from common cardiovascular and inflammatory risk factors. The role of MMP1 and its tissue inhibitors, should be tested further in prospective studies of cardiovascular disease.
Keywords: Cardiovascular diseases; Matrix metalloproteinase 1; Tissue inhibitor of metalloproteinase-1; Tissue inhibitor of metalloproteinase-2